Association of Post-Operative Lateral Skin Numbness after Total Knee Arthroplasty and Length of Skin Incision - Sangiamsak, MD, Seksit (Journal of Southeast Asian Orthopaedics, 2022)
Objectives: This study aimed to identify factors associated with lateral skin numbness after total knee arthroplasty (TKA), in particular, the length of the skin incision from the inferior margin of the patella and from the tibial tubercle to the inferior end of the skin incision including identification of common locations of numbness. The study also investigated the relationship between the diabetes status of the patient and the occurrence of numbness. Materials and Methods: A prospective analytic observational study was conducted with a total of 45 TKAs from 33 patients (12 bilateral, 21 unilateral) who had undergone primary TKA for primary osteoarthritis. All TKAs were performed by conventional surgical techniques. The length of the skin incision was determined based on the skin tension of each patient. The location of skin numbness was identified with the knee in 90 degrees of flexion using a blunt pin to elicit a pin-prick sensation. We performed pin-prick sensation tests at 4 areas: the upper and lateral border of the patella, the upper lateral half of the patella, the lower border of the patella inferiorly to the end of the incision and expanding laterally, and the lower half of the patella. Two skin incision lengths were measured. The length of the incision from the patella was defined as a the distance from the inferior border of the patella inferiorly to the end of the skin incision. The length of the incision from the tibial tubercle was measured from the tibial tubercle inferiorly to the end of the skin incision. Both incision lengths were measured intraoperatively and then were measured again during the first follow up visit at between 2 weeks and 1 month. Results: Among the 45 TKAs, 26 (57.78%) developed objective numbness. In the group of TKAs with numbness, the length of the incision from the lower patella was 7.13 cm. which was significantly longer than the 6.00 cm. in the group with no numbness. The mean length of the incision from the tibial tubercle in the numbness group was 2.88 cm. compared with 2.04 cm. in the no numbness group, a statistically significant difference. Of the 5 knees from 4 patients with well controlled DM, all had skin numbness. Of the TKAs with numbness, 100% had numbness on the lower border of the patella inferior to the incision, 57.69% had numbness in the lower half of the patella and 15.38% had numbness in the upper lateral half of the patella. Conclusions: A longer incision length is associated with a higher incidence of postoperative numbness. The incision lengths suggested in this study may potentially help reduce the incidence of short-term skin numbness complications after TKA.